The Social Media Discourse Analysis to improve Students' EFL Critical Thinking in Universitas Tridinanti - Budiyanto, Darmawan; Ridho, M. Rasyid (Universitas Indo Global Mandiri, 2024)
This study explores the impact of social media discourse analysis on enhancing the critical thinking skills of EFL (English as a Foreign Language) students at Universitas Tridinanti. A mixed-methods approach was employed, combining quantitative and qualitative data collection and analysis. The study involved 150 EFL students divided into control and experimental groups. Quantitative data were gathered through pre-test and post-test assessments, analysed using descriptive statistics, inferential statistics (paired and independent sample t-tests), and ANCOVA. Qualitative data were obtained from semi-structured interviews and documentation observation, involving 10 participants from the experimental group. Quantitative findings revealed a significant improvement in the critical thinking skills of students in the experimental group, with mean post-test scores increasing from 60 to 75, compared to a smaller increase in the control group. Qualitative results supported these findings, highlighting increased engagement, motivation, and enhanced critical thinking skills due to the interactive and collaborative nature of social media platforms. This research is novel in its focused application of social media discourse analysis within an EFL context at Universitas Tridinanti, providing context-specific insights and practical implications for similar educational settings. The integration of both quantitative and qualitative methods enriches the understanding of social media's educational impact. The study concludes that social media discourse analysis effectively improves EFL students' critical thinking skills at Universitas Tridinanti. Keywords: social media, discourse analysis, critical thinking, EFL students, mixed-methods